The Neglected “Other” within the “Other”: The Rise and Drive in the Songs of Poikayil Appachan - Syamchand, Soumy (International Journal of Psychosocial Rehabilitation, 2020)
India writing in English has traditionally embraced bionetwork, geography, sociology, and has often missed Dalit literary traditions. In the last few decades, literature has expanded its horizons to consider intersections between ecology, society and culture. However, the question still remains: why is there no recognition of organic underpinnings in the writings of subordinate castes by the wider canon of the environmental literary sphere? The aim of the present paper is to examine the varied underlined, invisible ways of suffering embedded in the lives of the Dalit community, particularly woman and their life experiences portrayed in The Songs of Poikayil Appachan. The age in which Poikayil lived was the age of struggle and transformation in Travancore. The caste system could not survive in the old form in the context created by colonial modernity. Different castes reacted against this context differently. During this age of renaissance, a number of social reformers were also born. In this context of Kerala renaissance Poikayil Appachan intervened with a unique theory and praxis which made him a separate entity in his time. The songs of Poikayil was not only presents the plight of the lower caste society but it also plays the role of a constant reminder of the hardships faced by the subaltern women in the society. Their condition is pitiable not only in Kerala but throughout India. The present study tries to envisage the reconstruction of prevailing unequal order, the songs of Poikayil is the saga of resistance against the hegemony of upper-class literature which pretends to be omniscient and all- encompassing while presenting a narrow, one sided, twisted and biased view of reality.